Early nutritional support and physiotherapy improved long-term self-sufficiency in acutely ill older patients - Hegerová, Petra; Dědková, Zuzana; Sobotka, Luboš (Nutrition (Burbank, Los Angeles County, Calif.), 2015)
OBJECTIVE: An acute disease is regularly associated with inflammation, decreased food intake, and low physical activity; the consequence is loss of muscle mass. However, the restoration of muscle tissue is problematic, especially in older patients. Loss of muscle mass leads to further decrease of physical activity which leads, together with recurring disease, to the progressive muscle mass loss accompanied by loss of self-sufficiency. Early nutrition support and physical activity could reverse this situation. Therefore, the aim of this study was to determine whether an active approach based on early nutritional therapy and exercise would influence the development of sarcopenia and impaired self-sufficiency during acute illness. METHODS: Two hundred patients >78 y were admitted to a hospital internal medicine department and participated in a prospective, randomized controlled study. The patients were randomized to a control group receiving standard treatment (n = 100) or to an intervention group (n = 100). The intervention consisted of nutritional supplements (600 kcal, 20 g/d protein) added to a standard diet and a simultaneous intensive rehabilitation program. The tolerance of supplements and their influence on spontaneous food intake, self-sufficiency, muscle strength, and body composition were evaluated during the study period. The patients were then regularly monitored for 1 y post-discharge. RESULTS: The provision of nutritional supplements together with early rehabilitation led to increased total energy and protein intake while the intake of standard hospital food was not reduced. The loss of lean body mass and a decrease in self-sufficiency were apparent at discharge from the hospital and 3 mo thereafter in the control group. Nutritional supplementation and the rehabilitation program in the study group prevented these alterations. A positive effect of nutritional intervention and exercise during the hospital stay was apparent at 6 mo post-discharge. CONCLUSIONS: The early nutritional intervention together with early rehabilitation preserves muscle mass and independence in ill older patients hospitalized because of acute disease.
Keywords: nutriční podpora; Self-sufficiency; Prospective Studies; Nutritional Support; senioři nad 80 let; index tělesné hmotnosti; Humans; Elderly; prospektivní studie; Aged, 80 and over; Dietary Supplements; Exercise; složení těla; Body Mass Index; Nutritional Status; Physical Therapy Modalities; potravní doplňky; Muscle Strength; techniky fyzikální terapie; Energy Intake; Dietary Proteins; cvičení; Body Composition; Sarcopenia; dietní proteiny; kritický stav; nutriční stav; Lean body mass; svalová síla; lidé; kosterní svaly; Critical Illness; Aged; Quality of Life; Muscle, Skeletal; senioři; energetický příjem; Nutrition; kvalita života; sarkopenie